Can rigid ureteroscopic lithotripsy be an alternative to flexible ureteroscopic lithotripsy in the treatment of isolated renal pelvis stones smaller than 2 cm? - Akkoç, Ali; Ucar, Murat (Journal of Surgery and Medicine, 2020)
Aim: Although flexible ureteroscopy (FURS) is preferred over rigid ureteroscopy in the treatment of kidney stones, rigid ureteroscopy (RURS) is also often sufficient for reaching the renal pelvis in many patients. In this study, we aimed to analyze the results of rigid (RURSL) and flexible ureteroscopic lithotripsy (FURSL) for the treatment of isolated renal pelvic stone (IRPS) <2 cm in size by evaluating stone-free rates, operation times, and associated complications. Methods: This retrospective cohort study included patients who underwent RURSL (group 1, n=24) and FURSL (group 2, n=21) for IRPS <2 cm in size between June 2012 and May 2017. RURS was routinely performed in all patients. The stones reached by rigid ureteroscope were fragmented with holmium laser. When the stones were not reachable by rigid ureteroscope, FURS was performed, and the stone was fragmented with the same laser energy. Results: In 24 of 45 (53.3%) patients, stones were reached by rigid ureteroscope and fragmented with holmium laser. In the remaining 21 (46.7%) patients, the stones could not be reached by rigid ureteroscope, and they were managed with FURS and fragmented with the same laser energy source. RURS was successful in reaching renal pelvic stones in 15 of 25 (60%) female patients; however, the stones were reached in 9 (45%) of 20 male patients (P=0.173). There was no significant difference between the two groups in terms of age, gender, side of stone, mean stone size, hospital stay, stone-free rates, and associated complications (P=0.298, P=0.396, P=0.775, P=0.266, P=0.742, P=0.428, P=0.186, respectively). The mean operative times were significantly lower in RURSL group than in FURSL group, and they were 66.75 (15.77) min and 89.54 (17.71) min, respectively (P<0.001). Conclusions: FURSL is a more appropriate procedure for the treatment of kidney stones; however, it should be kept in mind that RURSL is an alternative procedure to FURSL with shorter operation time, similar stone-free rates and similar complication rates for IRPS in selected cases.